Heterogeneity in Marginal Nonmonetary Returns to Higher Education - Daniel A. Kamhoefer; Hendrik Schmitz; Matthias Westphal (University of Duisburg-Essen, CINCH - Health Economics Research Center, 2015)
In this paper we estimate the effects of college education on cognitive abilities and health exploiting exogenous variation in college availability and student loan regulations. By means of semiparametric local instrumental variables techniques we estimate marginal treatment effects in an environment of essential heterogeneity. The results suggest heterogeneous but always positive effects on cognitive skills and homogeneously positive effects for all health outcomes but mental health, where the effects are around zero throughout. We find that likely mechanisms of positive physical health returns are effects of college education on physically demanding activities on the job and health behavior such as smoking and drinking while mentally more demanding jobs might explain the skill returns.
Keywords: C31; H52; I12; I21; 330; Returns to higher education; cognitive abilities; health; marginal treatment effect